2005
DOI: 10.1136/jnnp.2003.030536
|View full text |Cite
|
Sign up to set email alerts
|

Restless legs syndrome and low brain iron levels in patients with haemochromatosis

Abstract: Regional brain iron levels of two patients with haemochromatosis and severe restless legs syndrome (RLS) were assessed using R29 magnetic resonance imaging (MRI) sequences in both patients and in nine healthy controls. R29 relaxation rates in the patients were decreased in the substantia nigra, red nucleus, and pallidum when compared with the controls. These results indicate that local brain iron deficiency may occur in patients with haemochromatosis and suggest a role for brain iron metabolism in the pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 12 publications
0
29
0
2
Order By: Relevance
“…Values were decreased in the substantia nigra, red nucleus and pallidus in both patients compared with nine controls, suggesting an iron deficit in these regions. These findings revealed that, despite a high level of serum iron, local brain iron deficiency may occur in patients with HH, as if the blood-brain barrier is able to restrict the transport of the excess plasma iron to the brain [4,5].…”
mentioning
confidence: 90%
“…Values were decreased in the substantia nigra, red nucleus and pallidus in both patients compared with nine controls, suggesting an iron deficit in these regions. These findings revealed that, despite a high level of serum iron, local brain iron deficiency may occur in patients with HH, as if the blood-brain barrier is able to restrict the transport of the excess plasma iron to the brain [4,5].…”
mentioning
confidence: 90%
“…Several studies demonstrated an association between RLS and other conditions, including neurological diseases such as Parkinson disease (Ondo et al, 2002;Peeraully and Tan, 2012), dystonia (Paus et al, 2011), and attention deficit hyperactivity disorder (ADHD) (Cortese et al, 2005;Ming and Walters, 2009;Picchietti et al, 1999;Pullen et al, 2011;Silvestri et al, 2009;Walters et al, 2008;Zak et al, 2009); cardiovascular diseases such as hypertension (Schlesinger et al, 2009); and metabolic dysfunction such as iron deficiency Bhandal and Russell, 2006;Connor, 2008;Earley et al, 2000Earley et al, , 2005Haba-Rubio et al, 2005;Mizuno et al, 2005;Shaughnessy et al, 2005) XIII. RESTLESS LEGS SYNDROME and renal failure (Araujo et al, 2010;Marin et al, 2012;Quinn et al, 2011).…”
mentioning
confidence: 99%
“…Interestingly, the Btbd9 KO mice had elevated levels of iron in the serum. While this result is opposite of expected, not all RLS patients have iron alterations [25] and there is a subpopulation of RLS patients that have iron hemochromatosis, also known as iron overload [26, 27]. …”
Section: 0 Impact Of Btbd9 Modification On Rls-like Phenotypes In Micementioning
confidence: 99%